2019
DOI: 10.1177/0960327119833740
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA from a 12-h versus 20-h acetylcysteine infusion for paracetamol overdose

Abstract: Paracetamol overdose is common and microRNA (miR)-122 expression is increased with liver injury. We aimed to measure miR-122 in the setting of an abbreviated paracetamol overdose treatment regimen. We compared miRNA expression in patients treated for paracetamol poisoning with an abbreviated 12-h intravenous acetylcysteine regimen (200 mg/kg over 4 h, 50 mg/kg over 8 h) or a 20-h regimen (200 mg/kg over 4 h, 100 mg/kg over 16 h) (NACSTOP trial). miR-122 expression is increased (decreased cycle thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Others, like Wong et al [ 90 , 91 ], went further to assess the impact of dosing differently with NAC on paracetamol overdose. Here, they showed that in subjects receiving 12 h NAC regimen (200 mg/kg over 4 h, 50 mg/kg over 8 h) had similar circulating metabolite concentrations compared to a 20 h regimen in selected subjects with a low risk of hepatotoxicity.…”
Section: Protective Effects Of N-acetyl Cysteine Against Drug-induced Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Others, like Wong et al [ 90 , 91 ], went further to assess the impact of dosing differently with NAC on paracetamol overdose. Here, they showed that in subjects receiving 12 h NAC regimen (200 mg/kg over 4 h, 50 mg/kg over 8 h) had similar circulating metabolite concentrations compared to a 20 h regimen in selected subjects with a low risk of hepatotoxicity.…”
Section: Protective Effects Of N-acetyl Cysteine Against Drug-induced Liver Injurymentioning
confidence: 99%
“…Here, they showed that in subjects receiving 12 h NAC regimen (200 mg/kg over 4 h, 50 mg/kg over 8 h) had similar circulating metabolite concentrations compared to a 20 h regimen in selected subjects with a low risk of hepatotoxicity. Also, there was no observed liver injury or any effect on levels of ALT or miR-122 expression [ 90 , 91 ]. Besides assessing the impact of different doses, others reported on how NAC affects paracetamol when used in combination with other therapies.…”
Section: Protective Effects Of N-acetyl Cysteine Against Drug-induced Liver Injurymentioning
confidence: 99%
“…It is worth noting that the doses chosen for NAC and SIL, that is, 200 mg/kg, were due to two factors, one being a dose with a known hepatoprotective effect in others one-hit models of liver injury for both compounds [15][16][17][18][19][20] and because it is a dose that can be transferred to the clinic, given that the equivalent dose extrapolated allometrically would be 49 mg/kg for humans.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of SIL and NAC chosen was based in the dose with a known hepatoprotective effect in others one-hit models of liver injury for both compounds. [15][16][17][18][19][20] The weight of each animal was assessed during this time. Animals that had been administered xylazine (10 mg/kg) and ketamine (50 mg/kg) for anesthesia were punctured in the heart to collect blood.…”
Section: Lps and Ethanol Induce Liver Damagementioning
confidence: 99%
“…Significant changes in circulating miRNA profiles of various biologic matrices (e.g., blood, urine) have been demonstrated in mouse and rat models of acetaminophen toxicity [10][11][12]. In humans, key miRNAs have been notably upregulated in urine [13], hepatocytes [14,15], and blood [15][16][17][18][19][20]. Human studies have largely focused on liver-associated miRNAs, specifically miR-122, which has repeatedly been found to be elevated in acetaminophen hepatotoxicity [21,22].…”
Section: Introductionmentioning
confidence: 99%